2014
DOI: 10.1038/srep06339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of young poplar plantations on understory plant diversity in the Dongting Lake wetlands, China

Abstract: This study evaluated the effects of young poplar plantations on understory plant diversity in the Dongting Lake wetlands, China. Poplar plantations resulted in a higher species number and Shannon's diversity. Species compositions were different between areas with poplar and reed populations: a lower ratio of hygrophytes but a higher ratio of mesophytes, and a higher ratio of heliophytes but a lower ratio of neutrophilous or shade plants in poplar areas compared to reed areas. Poplar plantations supported a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
(52 reference statements)
1
20
0
1
Order By: Relevance
“…Most of the habitat indicator species identified in natural forests (Apet, Bsyl, Ccup, Eamy, Epar, Fulm, Gpal, Grob, Hlup, Lper, Lvul, Rcae, Rulm, Snig and Ssyl: see Figure 3 legend for explanation of the abbreviations) have previously been identified as having strict requirements of shade and/or soil moisture, even temporary flooding in some cases, which is typical of riparian zones [54,55]. Similar results were found in China, where the species composition of poplar plantations varied, resulting in a lower ratio of hygrophytes and a higher ratio of heliophytes [56].…”
Section: Comparison Between Riparian Forests and Poplar Plantationssupporting
confidence: 66%
“…Most of the habitat indicator species identified in natural forests (Apet, Bsyl, Ccup, Eamy, Epar, Fulm, Gpal, Grob, Hlup, Lper, Lvul, Rcae, Rulm, Snig and Ssyl: see Figure 3 legend for explanation of the abbreviations) have previously been identified as having strict requirements of shade and/or soil moisture, even temporary flooding in some cases, which is typical of riparian zones [54,55]. Similar results were found in China, where the species composition of poplar plantations varied, resulting in a lower ratio of hygrophytes and a higher ratio of heliophytes [56].…”
Section: Comparison Between Riparian Forests and Poplar Plantationssupporting
confidence: 66%
“…A large number of Populus plantations have accelerated the desiccation of wetland [4], resulting in a decrease of the wetland area [5][6][7]. This situation leads to the death of wetland vegetation [8]; induces biodiversity loss [7]; and influences the community composition [4], structure [7] and function [4] of the wetland ecosystem. Therefore, accurately detecting the land cover changes related to forests and then monitoring spatiotemporal dynamics of forests in the Dongting Lake region are critical for protecting wetland ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have found a decrease in species richness in plantations in comparison with (semi)natural communities (e.g. Van Wesenbeeck et al, 2003;Goldman et al, 2008;Paritsis and Aizen, 2008;Bremer and Farley, 2010;Proença et al, 2010;Quine and Humphrey, 2010) while cases of increase or equivalence seem to be uncommon (Bremer and Farley, 2010;Quine and Humphrey, 2010;Li et al, 2014). Exotic understorey plants with broad niche breadth are often much more abundant and diverse in plantations than in natural forests (Bremer and Farley, 2010).…”
Section: Introductionmentioning
confidence: 99%